Heavy metal pollution caused by small-scale metal ore mining activities: A case study from a polymetallic mine in South China - Sun, Zehang; Xie, Xiande; Wang, Ping; Hu, Yuanan; Cheng, Hefa (The Science of the total environment, 2018)
Although metal ore mining activities are well known as an important source of heavy metals, soil pollution caused by small-scale mining activities has long been overlooked. This study investigated the pollution of surface soils in an area surrounding a recently abandoned small-scale polymetallic mining district in Guangdong province of south China. A total of 13 tailing samples, 145 surface soil samples, and 29 water samples were collected, and the concentrations of major heavy metals, including Cr, Mn, Co, Ni, Cu, Zn, As, Cd, Pb, and Se, were determined. The results show that the tailings contained high levels of heavy metals, with Cu, Zn, As, Cd, and Pb occurring in the ranges of 739–4.15 × 103, 1.81 × 103–5.00 × 103, 118–1.26 × 103, 8.14–57.7, and 1.23 × 103–6.99 × 103 mg/kg, respectively. Heavy metals also occurred at high concentrations in the mine drainages (15.4–17.9 mg/L for Cu, 21.1–29.3 mg/L for Zn, 0.553–0.770 mg/L for Cd, and 1.17–2.57 mg/L for Pb), particularly those with pH below 3. The mean contents of Cu, Zn, As, Cd, and Pb in the surface soils of local farmlands were up to 7 times higher than the corresponding background values, and results of multivariate statistical analysis clearly indicate that Cu, Zn, Cd, and Pb were largely contributed by the mining activities. The surface soils from farmlands surrounding the mining district were moderately to seriously polluted, while the potential ecological risk of heavy metal pollution was extremely high. It was estimated that the input fluxes from the mining district to the surrounding farmlands were approximately 17.1, 59.2, 0.311, and 93.8 kg/ha/yr for Cu, Zn, Cd, and Pb, respectively, which probably occurred through transport of fine tailings by wind and runoff, and mine drainage as well. These findings indicate the significant need for proper containment of the mine tailings at small-scale metal ore mines. [Display omitted] •Heavy metal pollution in a small-scale metal ore mining area was investigated.•Pollution generally decreased with increasing distance from the mining district.•Cu, Zn, Cd, and Pb in local farmland soils came primarily from the mining activities.•Heavy metal pollution of local farmland soils posed high potential ecological risk.•Significant attention needs to be paid to the dumped tailings of small-scale mines.